Private Equity, Layoffs, and Job Polarization - Olsson, Martin; Tåg, Joacim (Journal of Labor Economics, 2017)
Private equity firms are often criticized for laying off workers, but the evidence on who loses their jobs and why is scarce. This paper argues that explanations for job polarization also explain layoffs after private equity buyouts. Buyouts reduce agency problems, which triggers automation and offshoring. Using rich employer-employee data, we show that buyouts generally do not affect unemployment incidence. However, unemployment incidence doubles for workers in less productive firms who perform routine or offshorable job tasks. Job polarization is also much more marked among workers affected by buyouts than for the economy at large.